2007
DOI: 10.1007/s00128-007-9198-3
|View full text |Cite
|
Sign up to set email alerts
|

Icefish (Salangidae) as an Indicator of Anthropogenic Pollution in Freshwater Systems Using Nitrogen Isotope Analysis

Abstract: We investigated differences in delta(15)N of seston and icefishes from seven freshwater ecosystems with different trophic states in China. An increase of seston delta(15)N values was accompanied by an increase of total nitrogen and phosphorus concentrations. Significantly positive correlations were observed between delta(15)N of icefishes and delta(15)N of seston, total nitrogen and phosphorus concentrations. This study demonstrated that icefishes could be preferred indicators of anthropogenic contamination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Hence, the assessment of anthropogenic pollution in aquatic ecosystems with the ı 15 N isotopic method has been widely tested on organisms of different trophic levels as biological indicators in aquatic ecosystems, including plants, invertebrates, and fishes (Lake et al, 2001;Cole et al, 2004;Schlacher et al, 2005;Xu et al, 2007). In addition the elevated ı 15 N signatures in aquatic biota are known to be correlated with increased exposure to human septic or sewage waste (Cole et Oligochaete Chironomus …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the assessment of anthropogenic pollution in aquatic ecosystems with the ı 15 N isotopic method has been widely tested on organisms of different trophic levels as biological indicators in aquatic ecosystems, including plants, invertebrates, and fishes (Lake et al, 2001;Cole et al, 2004;Schlacher et al, 2005;Xu et al, 2007). In addition the elevated ı 15 N signatures in aquatic biota are known to be correlated with increased exposure to human septic or sewage waste (Cole et Oligochaete Chironomus …”
Section: Discussionmentioning
confidence: 99%
“…Further, different nitrogen integration periods across multiple organisms can offer a selection of complementary vantage points for evaluating anthropogenic waste input at various spatial and temporal scales, which can help give focus on nutrient management (Gustafson et al, 2007;Wen et al, 2010). Meanwhile, the elevated ı 15 N signatures in primary consumers in aquatic ecosystems with anthropogenic nitrogen input will be further recorded by consumers higher up the food chain, such as fish, and result in elevated ı 15 N signatures of aquatic systems (Lake et al, 2001;Schlacher et al, 2005;Xu et al, 2007;Bergfur et al, 2009).…”
Section: ı 15 N Of Primary Consumers As An Bioindicatormentioning
confidence: 99%
See 1 more Smart Citation
“…N sources from human and animal waste usually have higher d 15 N than other N sources (McClelland et al 1997;McClelland and Valiela 1998). In our study, the higher pond smelt d 15 N values in Lake Youngrang and Lake Mae compared to Lake Hwajinpo might be due to differences in N sources from the watersheds (Cabana and Rasmussen 1996;Choi et al 2007;Xu et al 2010). Lake Youngrang and Lake Mae receive N inputs from sources such as waste water and agricultural runoff, but not in Lake Hwajinpo.…”
Section: Isotopic Differences In Pond Smelt In Brackish Lagoonsmentioning
confidence: 48%
“…Some studies have successfully used 15 N measurements of fish tissue to identify N sources to aquatic ecosystems. Xu et al (2010) showed that the d 15 N of icefish (Salangidae) could be used as an indicator to assess anthropogenic nutrient inputs based on the positive correlation between icefish d 15 N values and seston d 15 N values in freshwater ecosystems. Schlacher et al (2005) also found that fish tissue d 15 N values can be an excellent indicator of anthropogenic N in estuaries.…”
Section: Introductionmentioning
confidence: 99%